$L_p$ -dual mixed affine surface areas - Wan, Xiaoyan; Wang, W. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
Lutwak proposed the notion of $L_p$-affine surface area according to the Lp-mixed volume. Recently,Wang and He introduced the concept of Lp-dual affine surface area combing with the $L_p$-dual mixed volume. In the article, we give the concept of $L_p$-dual mixed affine surface areas associated with the $L_p$-dual mixed quermassintegrals. Further, some inequalities for the $L_p$-dual mixed affine surface areas are obtained.